Sensitivity of economists during market allocation - Johannes R. Suttner (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2014)
In this study, it was found that economists were sensitive to different commodities based on their attitudes in terms of fairness toward the price mechanism, whereas non-economists did not exhibit significant sensitivity. This sensitivity was so strong that no self-selection effect could be found in economists in the case of a survey of a basic commodity, whereas there was a clear self-selection effect with a luxury commodity. After one semester with intensive expo-sure to microeconomic theory, the market affinity of economists increased in both cases, but their sensitivity persisted. Surprisingly, it was the allocation mechanism of "first come, first served" and not the price mechanism that was affected more in terms of fairness. The latter reflects equal treatment in terms of general perceptions, thus this could be interpreted as an increased aversion to inequality among economists.
Keywords: A12; A13; A20; D63; R49; 330; attitude change; economics teaching; fairness; selection